ANALISIS PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI ALAT PERENCANAAN DAN PENGENDALIAN PADA HOTEL SANTIKA KOTA BENGKULU - Een Wahyudi; Nina Yulianasari (Universitas Prof.Hazairin,SH Bengkulu, 2019)
This study aims to assess the application of accountability accounting as a planning and control tool at the Santika hotel in the city of Bengkulu. The method of data analysis uses Quantitative Descriptive Analysis using a formula from Dean J. Champion. From the calculation results obtained, the application of accountability accounting as a planning tool at the Santika hotel in Bengkulu city has been very good, it can be seen from the results of statistical analysis of accountability accounting data as a plan that shows a percentage of 95.3%, this is appropriate because the Santika hotel in Bengkulu has clear organizational structure, delegation of authority and responsibility, has separated the centers of accountability, managers are given a role in achieving goals, making plans with budgeting, budgeting can motivate managers to improve performance, coordination between parts, and comparing budgets with the realization. The application of accountability accounting as a controlling tool in Santika hotels in Bengkulu city has been very good, this can be seen from the results of statistical analysis of accountability accounting data as a control which shows a percentage of 96.2%, this is appropriate because Santika hotel Bengkulu city has recorded transactions with codes account, do the separation between controlled and uncontrolled costs, each part has given an accountability report, in the reporting system has separated between the still planned with the realization reported periodically, the accountability report is the realization of the budget prepared previously, deviations that occur are always analyzed and the cause is sought, the results of the deviation analysis are used as the basis for managers to take corrective actions, there are special bonus incentives given to outstanding managers.